Hubungan Obesitas Dengan Kejadian Infark Serebral Pada Pasien Rawat Inap Bangsal Saraf RSUD Dr. Moewardi - C N, Stefanny; Prasodjo, JB; Hudiyono, . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background Â :Obesity is closely associated with increased risk of atherosclerosis disease. Atherosclerosis occurs when a portion of the surface of the large arteries forming plaque. As a result, the plaque will cause blood vessel disorders, even cerebrovascular disease. Cerebral infarction is a cerebrovascular disease that can cause a drop in the supply of oxygen and glucose to a particular part of the brain that eventually lead to the onset of a stroke. The cerebral infarctionâs high occurrence rate were the reason that made the researcher wanted to find out if there is a relationship between obesity and cerebral infarction in patients hospitalized in the neurological ward RSUD Dr.Moewardi. Methods :This was an observational analytic research with cross sectional design. This research was done in RSUD Dr.Moewardi. The sampling was done in consecutive sampling. This researchâs populations were patients hospitalized in the neurological ward RSUD Dr.Moewardi during November-December 2012. Results :Total sample are 42 patients. The result of this research shows there were 21 samples of cerebral infarction case, which consisted of 17 obesity patients and 4 non-obesity patients. The other 21 samples were the non-cerebral infarction patients which consisted of 3 obesity patients and 18 non-obesity patients. The obtained data were analyzed using Chi-Square test and resulted in a significant relationship ( p< 0,01). Conclusions :There was a relationship between obesity and cerebral infarction in patients hospitalized in the neurological ward RSUD Dr.Moewardi. Key words :relationship, obesity, cerebral infarction.